Dampak Marketing Mix terhadap Minat Pembelian Sayur Hidroponik Pada PT. Anugerah Bumi Trawas di Surabaya - Anky Fibrianti; Harsono Teguh; Bambang Karnain; Rina Dewi; Achmad Daengs GS (Jurnal Mahasiswa Manajemen dan Akuntansi, 2024)
This research aims to investigate and analyze the impact of the marketing mix on purchasing interest of hydroponic vegetables at PT Anugerah Bumi Trawas, Surabaya. The study employs a descriptive-analytical approach with a quantitative method. Involving 75 respondents selected through purposive sampling, data were collected using an online Google questionnaire. Data analysis includes multiple linear regression, descriptive analysis, normality test, hypothesis testing, and coefficient of determination. The research findings indicate that product (X1), price (X2), and distribution (X4) significantly influence purchasing interest, while promotion (X3) does not. Simultaneously, product (X1), price (X2), promotion (X3), and distribution (X4) collectively have a significant impact on purchasing interest in Surabaya, with product (X1) being the dominant variable. The implication of this study is to enhance purchasing interest at PT Anugerah Bumi Trawas, Surabaya.